PENINJAUAN SISTEM POLDER GROGOL DALAM MENGHADAPI BANJIR - Vittorio Kurniawan; Wati Asriningsih Pranoto; Fernando Putra Ongga (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Floods that often occur due to high rainfall inflicts social problems and other social impacts on the community. Therefore. a capable drainage system is necessary which comprises drainage channels with adequate capacities as well as pumps with sufficient capacities and operational rules. The study focuses on hydrological and hydraulical analysis on the system of Polder Grogol, West Jakarta. The estimation of design flood discharge employs Soil Conservation Service method with 5 years return period for Semeru and Makaliwe channels. The results of hydraulical analysis shows both channels are still adequate in draining design flood discharge. However, the existing pumping system is no longer sufficient to keep the reservoir’s water level below the bottom of reservoir’s inlet channel. There are several options to lower the reservoir water level. In this study, the approach is to add a new pump with the capacity of 0,25 m3/s wihout changing the formation of existing pumps. The analysis results reveals the additional pump manages to lower the reservoir water level below the targeted elevation.